(untitled) (International Journal of Engineering and Computer Science, 2016)
Language is used as a mode of communication by human beings. Through language we can directly express our various mental and emotional sates. In this paper, E.S.R.T.A. tries to detect the emotional state of a user through text and respond by displaying web pages and multimedia to improve or support the mood of a user. It also tries to give a brief introduction to a new idea called SMART technology. This can help to improve human-computer interaction.